Impact of Mercury Exposure on SGOT and SGPT Levels on Traditional Gold Miners - Aini, Aini; Yuliana, Yuliana; Atfal, Bustanul (JSN : Jurnal Sains Natural, 2024)
Mercury (Hydragyrum) is a heavy metal element that has received major attention in terms of health because it is toxic to humans. The main health problems caused by mercury vapor occur in the brain, lungs, central nervous system and kidneys. The aim of this research is to determine the impact of mercury exposure on SGOT and SGPT levels on traditional gold miners using the correlation method with a cross sectional approach. The population in this study is traditional gold miners. A total of 30 people were taken as samples in this study using purposive sampling technique. Data collection uses questionnaires and blood sampling. Data analysis test using the Chi-Square test with the help of SPSS. Based on the results of the questionnaire and taking blood samples from respondents with exposure to mercury, the sample was 30 respondents, Normal SGOT 15 respondents (50%) and abnormal SGOT 15 respondents (50%), while taking blood samples from 30 respondents with exposure to mercury with abnormal SGPT levels was 14 respondents. (46.7%) and normal SGPT levels in 16 respondents (53.3%). The results of the analysis used the Chi Square test with the help of SPSS version 20, the number of respondents was 30 people. The significant level obtained was for SGOT p=0.001, then, p < (0.001< 0.05), and for SGPT p=0.001, then, p <( 0.001 < 0.05), this shows that mercury exposure has a significant impact on SGOT and SGPT levels in traditional gold miners.